Change in Police Attendance at Overdose Events following Implementation of a Police Non-Notification Policy in British Columbia - Amiti Mehta; Jessica C. Xavier; Heather Palis; Amanda Slaunwhite; Sandra Jenneson; Jane A. Buxton (Advances in Public Health)
Introduction. Bystanders at overdose events often hesitate to call 911 due to fear of police involvement. To address this, in 2016, British Columbia Emergency Health Services (BCEHS) introduced a policy to not routinely inform police of overdose events. This study explores change in police attended overdose events after the policy was implemented. Methods. Data on police attended overdose events were derived from naloxone administration forms in BC’s Take-Home Naloxone (THN) kits returned before and after the policy change. Segmented regression was conducted to quantify change in police attended overdose events. Results. The average proportion of police attended overdose events pre-policy was 55.6% compared to 37.9% post-policy. The segmented regression model demonstrated a 0.98% (95% CI: (−1.70 to −0.26)) decline (p=0.01) in police attended overdose events each month following the policy. Conclusion. Our findings suggest that the BCEHS policy contributed to a decrease in police attended overdose events.